2020
DOI: 10.1103/physrevlett.124.101103
|View full text |Cite
|
Sign up to set email alerts
|

Universal Relation between Corrections to Entropy and Extremality

Abstract: Perturbative corrections to General Relativity alter the expressions for both the entropy of black holes and their extremality bounds. We prove a universal relation between the leading corrections to these quantities. The derivation is purely thermodynamic and the result also applies beyond the realm of gravitational systems. In scenarios where the correction to the entropy is positive, our result proves that the perturbations decrease the mass of extremal black holes, when holding all other extensive variable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
84
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 18 publications
8
84
1
Order By: Relevance
“…We have found that the entropy shift is always positive for this family of solutions. In previous works in the literature, it has been claimed that the positivity of the corrections to the entropy imply a positive correction to the charge-to-mass ratio at extremality [31][32][33]. On the contrary, this claim has been disputed by the counterexample presented in Ref.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have found that the entropy shift is always positive for this family of solutions. In previous works in the literature, it has been claimed that the positivity of the corrections to the entropy imply a positive correction to the charge-to-mass ratio at extremality [31][32][33]. On the contrary, this claim has been disputed by the counterexample presented in Ref.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, according to the prescription given in Ref. [33], the right hand side of (7.2) must be evaluated taking M to be slightly larger than the unperturbed extremal limit, which is denoted as M ≈ M (0) ext , defined such that the corrections to the temperature at fixed mass and charges are subdominant. In the particular case we study in this article, this could be expressed as follows,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scalar fields usually affect the thermodynamic description of black holes -see e.g. [39] -and it would be interesting to explore whether this could modify the conclusions of [23]. The string coupling constant and the curvature can be kept sufficiently small in the exterior region of the black hole for the cases we have considered, hence the low energy field theory description gives a good approximate description of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent works have proposed that, demanding analyticity of scattering amplitudes, unitarity and causality constrain these coefficients such that there is a positive deviation of the charge-to-mass ratio of extremal black holes [18][19][20]. Likewise, it has been proposed that this can be related to the positivity of the corrections to the entropy of the black hole induced by higher-derivative operators [21][22][23]. The study of black holes in Einstein-Maxwell theory is well justified and interesting, as it provides a relatively simple arena to explore this question while making contact with dominant interactions in real world experiences.…”
Section: Introductionmentioning
confidence: 99%